2014
DOI: 10.1542/peds.2014-0318
|View full text |Cite
|
Sign up to set email alerts
|

Patient- and Family-Centered Care Coordination: A Framework for Integrating Care for Children and Youth Across Multiple Systems

Abstract: Understanding a care coordination framework, its functions, and its effects on children and families is critical for patients and families themselves, as well as for pediatricians, pediatric medical subspecialists/ surgical specialists, and anyone providing services to children and families. Care coordination is an essential element of a transformed American health care delivery system that emphasizes optimal quality and cost outcomes, addresses family-centered care, and calls for partnership across various se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(99 citation statements)
references
References 30 publications
2
97
0
Order By: Relevance
“…This is consistent with recommendations from the American Academy of Pediatrics' policy statement on care coordination. 8 Previous studies examined care coordination at 1 point in time, capturing the range of activities, volume, and cost to practices, 21 but not how care coordination changes as a practice's medical home model matures. We found that creation and installation of tools and practices for proactive activities typically followed some study or consideration of recurring issues faced by care coordinators and planning, including some trial and error, by medical home teams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with recommendations from the American Academy of Pediatrics' policy statement on care coordination. 8 Previous studies examined care coordination at 1 point in time, capturing the range of activities, volume, and cost to practices, 21 but not how care coordination changes as a practice's medical home model matures. We found that creation and installation of tools and practices for proactive activities typically followed some study or consideration of recurring issues faced by care coordinators and planning, including some trial and error, by medical home teams.…”
Section: Discussionmentioning
confidence: 99%
“…2 The scope and definition of "care coordination" have evolved, [3][4][5][6][7] and the 2014 American Academy of Pediatrics policy statement offers a framework, emphasizing patient-and familycenteredness, working in teams across medical and other settings, and enhancing families' capabilities. 8 This was part of a larger study to examine change toward the medical home model. 9 We used a positive deviance approach 10,11 and mixed methods 12,13 to examine successful practices that had participated in a national medical home learning collaborative in 2003 to identify factors or processes that contributed to implementation that could then be translated to other practices.…”
mentioning
confidence: 99%
“…Measurably, 100% of families referred have made appointments for follow-up within 48 hr, with most behavioral health appointments being arranged before departing the clinic. Evidence for the importance of care coordination in promoting follow-through is accumulating rapidly (Silverstein et al, 2015;Turchi et al, 2014), and it is emphasized as a central aspect of the Collaborative's system development. In addition, measurement of concrete behaviors related to this construct are tracked through program evaluation efforts, including engagement, treatment adherence, early dropout rate, and appointment efficiency.…”
Section: Goal 1: Establish and Enhance Efficient Multidisciplinary Carementioning
confidence: 99%
“…Both of these frameworks focus on strengthening integration of health services and systems (e.g., public health, clinical, and community) to break down siloes and to engage and empower patients and their families to optimize health outcomes. The AAP has called for the integration and coordination of care between clinical health care and community settings, such as WIC, that is centered on the comprehensive needs of the patient and family leading to a reduction in fragmented, inconsistent care [27]. …”
Section: Introductionmentioning
confidence: 99%